Measuring Participation: The Patient-Reported Outcomes Measurement Information System Experience - Bode, Rita K. (2010)
OBJECTIVES: To describe the lessons learned in the initial development of PROMIS social function item banks. DESIGN: Development and testing of two item pools within a general population to create item banks that measure ability-to-participate and satisfaction-with-participation in social activities. SETTING: Administration via the Internet. PARTICIPANTS: General population members (N=956) of a national polling organization registry participated; data for 768 and 778 participants used in the analysis. INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURES: Measures of ability-to-participate and satisfaction-with-participation in social activities. RESULTS: Fifty six items measuring the ability-to-participate were essentially unidimensional but did not fit an IRT model. As a result, item banks were not developed for these items. Of the 56 items measuring satisfaction-with-participation, 14 items measuring social roles and 12 items measuring discretionary activities were unidimensional and met IRT model assumptions. Two 7-item short forms were also developed. CONCLUSIONS: Four lessons, mostly concerning item content, were learned in the development of banks measuring social function. These lessons led to item revisions that are being tested in subsequent studies.